2008
DOI: 10.1097/tp.0b013e318186b978
|View full text |Cite
|
Sign up to set email alerts
|

Operational Tolerance in Nonvascularized Transplant Models Induced by AR-C117977, a Monocarboxylate Transporter Inhibitor

Abstract: AR-C117977, a monocarboxylate transporter inhibitor, reduces immune responses both in vitro and in vivo, maintains long-term graft survival, and induces operational tolerance. To evaluate the immunosuppressive limitations of AR-C117977, this study was performed in nonvascularized transplant models noted for their refractive response to standard immunosuppressive agents. Rat skin was transplanted from DA(RT1avl) into PVG(RT1c) and the reverse. Mouse islet allotransplantation was performed with BALB/c H2d donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…[295] Nevertheless, compound 86 , also known as AR-C117977, showed efficient immunosuppressive activities both in vitro and in vivo. [296] The structural optimization of these compounds led to the production of a less lipophilic and more water soluble derivative, AR-C155858 ( 89 ). This compound proved to efficiently bind to MCT1 with a K i value of 1.2 nM (human erythrocytes), and to potently inhibit both MCT1 and MCT2, by binding to an intracellular site of these transporters.…”
Section: Glycolytic Effectors As Potential Targets In Cancer Therapymentioning
confidence: 99%
“…[295] Nevertheless, compound 86 , also known as AR-C117977, showed efficient immunosuppressive activities both in vitro and in vivo. [296] The structural optimization of these compounds led to the production of a less lipophilic and more water soluble derivative, AR-C155858 ( 89 ). This compound proved to efficiently bind to MCT1 with a K i value of 1.2 nM (human erythrocytes), and to potently inhibit both MCT1 and MCT2, by binding to an intracellular site of these transporters.…”
Section: Glycolytic Effectors As Potential Targets In Cancer Therapymentioning
confidence: 99%
“…Påhlman et al 21 evaluated the immunosuppressive limitations of AR-C117977, a immunosuppressant drug that maintains long-term graft survival and induces operational tolerance, and concluded that AR-C117977 combined with CsA resulted in significant prolongation of graft survival when compared with AR-C117977 or CsA monotherapy. Furthermore, CsA monotherapy did not avoid acute rejection.…”
Section: B Resultsmentioning
confidence: 99%
“…Jung et al 26 Balb/c → C57Bl/6 CD154 mAb (MR1) anti-ratos e ROS-A (Reactive Oxygen Specie-A) Cápsula renal ROS-A -53 dias, MR1 -82 dias, ROS-A+MR1 ->160 dias Påhlman et al 27 Balb/c → C57Bl/6J AR-C117977 (10 ou 30 mg/kg) ou CsA 20 mg/kg Cápsula renal CsA -16 dias AR-C117977, 10 mg/kg->100dias AR-C117977, 30 mg/kg -29,33 dias Wang et al 28 Balb/c → C57Bl/6 B7-H4 e Ad-LacZ Cápsula renal B7-H4 -aproximadamente 60 dias Ad-LacZaproximadamente > 20 dias …”
Section: Cápsula Renal 70%mentioning
confidence: 99%